Implanta????o de software para prescri????o eletr??nica em uma farm??cia de manipula????o especializada em nutri????o parenteral - Rafael, Deivid Nogueira (2017)
Errors involving medications are frequent in health care, causing preventable adverse events of different severities. In this case, prescriptions have great importance in this prevention when elaborated in a readable and complete form. Among the evolutions of the digital era in health care, one of them is the electronic prescription, which is the procedure where the prescriber elaborates the prescription using dedicated software and sends it by electronic means. The objective of this work was to analyze the evolution of the implantation of electronic prescription software in a compounding center, specialized in the preparation of parenteral nutrition. Qualitative exploratory and quantitative descriptive approaches were adopted in a single case study. In the qualitative approach, structured interviews were elaborated, based on theoretical assumptions, applied to the managers and the responsible for Software development. For the evaluation of the data and compilation of the results, a content analysis was used, grouping the questions by similarity and by creating categories. In the quantitative approach, a survey was made about the number of "deviations" in the period from 2006 to 2015, evaluating the impact of the implementation of electronic prescriptions and a comparison with the prescriptions sent by fax and e-mail. The obtained results indicated that the use of electronic prescription software and pharmacist care reduces considerably the number of deviations in prescriptions. The electronic prescription acts as an important tool to help the prescriber to reduce redoing prescriptions as well as possible errors of interpretation when compared to prescriptions sent manually by fax or e-mail.